Acupuncture for the Treatment of Pain – A Mega-Placebo? - Musial, Frauke (Frontiers in Neuroscience, 2019)
Several control conditions, such as penetrating sham acupuncture and non-penetrating placebo needles, have been used in clinical trials on acupuncture effects in chronic pain syndromes. All these control conditions are surprisingly effective with regard to their analgesic properties. These findings have fostered a discussion as to whether acupuncture is merely a placebo. Meta-analyses on the clinical effectiveness of placebo revealed that placebo interventions in general have minor, clinically important effects. Only in trials on pain and nausea, including acupuncture studies, did placebo effects vary from negligible to clinically important. At the same time, individual patient meta-analyses confirm that acupuncture is effective for the treatment of chronic pain, including small but statistically significant differences between acupuncture and sham acupuncture. All acupuncture control conditions induce de qi, a distinct stimulation associated with pain and needling which has been shown to be a nociceptive/pain stimulus. Acupuncture therefore probably activates the pain matrix in the brain in a bottom-up fashion via the spino-thalamic tract. Central nervous system effects of acupuncture can be modulated through expectations, which are believed to be a central component of the placebo response. However, further investigation is required to determine how strong the influence of placebo on the attenuation of activity in the pain matrix really is. A meta-analysis of individual participant functional magnetic imaging data reveals only weak effects of placebo on the activity of the pain network. Conclusion: The clinical acupuncture setting is comprised of a combination of a distinct neurophysiological stimulus, the needling stimulus/experience, and a complex treatment situation. A broader definition of placebo, such as that proposed by Howick (Howick 2017) acknowledges a role for expectation, treatment context, emotions, learning and other contextual variables of a treatment situation. The inclusion of particular treatment feature as a definitional element permits a contextual definition of placebo, which in turn can be helpful in constructing future clinical trials on acupuncture.